1984
DOI: 10.1080/14640748408402180
|View full text |Cite
|
Sign up to set email alerts
|

Timing in Solo and Duet Piano Performances

Abstract: Perhaps some of the most refined forms of timing arise in musical performance, particularly in the coordination between musicians playing together. Studies of timing in solo and duet piano performances are described, in which the musicians gave repeat performances of the music. In both solo and duet performances there was expressive use of timing, modulating the tempo of the music and the phase relationship between the voices, and the expressive forms were similar in successive performances of the piece. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
0
7

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(89 citation statements)
references
References 11 publications
1
81
0
7
Order By: Relevance
“…Analyses of musical performances reveal similar findings. Numerous studies have shown that pianists display salient changes in amplitude, tempo, and tonal prolongation at melodic phrase boundaries nested within the underlying tonality scheme (e.g., Clarke, 1982Clarke, , 1988Gabrielsson, 1988;Shaffer, 1981Shaffer, , 1984Sundberg, 1988;Todd, 1985). Such findings suggest that the individual producing an event may rely on a hierarchical motor scheme that temporally highlights the intended meaning.…”
Section: Discussionmentioning
confidence: 97%
“…Analyses of musical performances reveal similar findings. Numerous studies have shown that pianists display salient changes in amplitude, tempo, and tonal prolongation at melodic phrase boundaries nested within the underlying tonality scheme (e.g., Clarke, 1982Clarke, , 1988Gabrielsson, 1988;Shaffer, 1981Shaffer, , 1984Sundberg, 1988;Todd, 1985). Such findings suggest that the individual producing an event may rely on a hierarchical motor scheme that temporally highlights the intended meaning.…”
Section: Discussionmentioning
confidence: 97%
“…The significance of feedback in musical performance is a complex matter that has been studied relatively little (Shaffer, 1984). The stimulus sequences in experiments like ours should be more multifarious (multitonal and with more durations) to study this problem more adequately.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of quantitative research on detailed aspects of expressive performance, based on measurements of timing, dynamics, etc., has been done in recent decades (e.g., Shaffer, 1981Shaffer, , 1984Shaffer et al, 1985;Clarke, 1985;Gabrielsson, 1987;Palmer, 1989Palmer, , 1996aRepp, 1992Repp, , 1995Repp, , 1998Repp, , 1999Goebl, 2001, to name but a few). Some of this work is descriptive rather than predictive, focusing on measuring performance details and describing classes of common patterns, often with the help of statistical analysis.…”
Section: Computational Modelling Of Expressive Music Performancementioning
confidence: 99%